2011
DOI: 10.1371/journal.pone.0025268
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chaperone Mediated Autophagy (CMA) in the Degradation of Misfolded N-CoR Protein in Non-Small Cell Lung Cancer (NSCLC) Cells

Abstract: Nuclear receptor co-repressor (N-CoR) plays important role in transcriptional control mediated by several tumor suppressor proteins. Recently, we reported a role of misfolded-conformation dependent loss (MCDL) of N-CoR in the activation of oncogenic survival pathway in acute promyelocytic leukemia (APL). Since N-CoR plays important role in cellular homeostasis in various tissues, therefore, we hypothesized that an APL like MCDL of N-CoR might also be involved in other malignancy. Indeed, our initial screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…Certain studies suggest that the pro-survival functions of autophagy decrease the efficacy of cancer therapeutics (20,25). However, other studies have demonstrated that autophagy also induced cancer cell death after various treatments (9,(28)(29)(30). Thus, activation of autophagic cell death is becoming an important strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies suggest that the pro-survival functions of autophagy decrease the efficacy of cancer therapeutics (20,25). However, other studies have demonstrated that autophagy also induced cancer cell death after various treatments (9,(28)(29)(30). Thus, activation of autophagic cell death is becoming an important strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, later experiments revealed that the multimerization of LAMP-2A is transient and that as soon as the substrate is translocated into the lumen, LAMP-2A disassembles from this complex in an hsc70-dependent manner [20]. The multimeric complex that mediates substrate translocation is of a defined size (700 kDa) and is composed mainly of LAMP-2A molecules but at least two other proteins can also be found associated to the complex [22,23] ( Kon et al, unpublished). Interestingly, these additional components seem important to regulate the stability of the multimeric complex but not essential for translocation, as inserting LAMP-2A in proteoliposomes in the presence of hsc70 is sufficient to mediate substrate translocation, although understandably at a lower efficiency than lysosomes (Cuervo AM and Dice JF, unpublished).…”
Section: How Does Cma Work?mentioning
confidence: 99%
“…Lastly, it is possible that in other tumors, part of the negative consequences of CMA blockage are due to reduced quality control. While in many cancer cell types, prolonged blockage of CMA elicits upregulation of the ubiquitin proteasome system (UPS), thus preventing accumulation of damaged substrates normally degraded by CMA [35], in other types of cancers, accumulation of oxidized and misfolded proteins has been proposed to underlie the toxic effect of CMA blockage [23,64]. The upregulated CMA in these latter cells helps to ameliorate intracellular stress and promotes the activation of oncogenic survival pathways [23].…”
Section: Abnormally Enhanced Cma and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this motif is a pattern recognition motif associated with the hydrophobicity and charge of amino acid residues, rather than 100 % compliance with specific amino acid residues [26]. Interestingly, post-translational modification could perfect some KFERQ-similar motif for CMA through changing the hydrophobicity and charge of amino acid residues [27]. Briefly, CMA can be divided into four main steps: recognition, unfolding, translocation and degradation [28].…”
Section: Autophagymentioning
confidence: 99%